2012
DOI: 10.1002/pen.23306
|View full text |Cite
|
Sign up to set email alerts
|

Uni‐ and biaxial impact behavior of double‐gated nanoclay‐reinforced polypropylene injection moldings

Abstract: Polypopylene/nanoclay three-dimensional parts were produced without intermediate steps by direct injection molding to explore the influence of flow features and nanoclay incorporation in their impact performance. The nanocomposite was obtained by direct compounding of commercial PP with nanoclay masterbatch. The as-molded morphology was analyzed by X-ray and TEM analyses in terms of skin-core structure and nanoclay particle dispersion. The nanoclay particles induced the reduction of b-form spherulites, a known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In our previous investigations conducted on PP/organoclay nanocomposite moldings – carried out on pieces that included a weld line – we found that nanoclay induces changes in the morphology developed upon processing . It enhances molecular orientation induced by flow increasing the level of crystalline phase orientation in the flow direction.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous investigations conducted on PP/organoclay nanocomposite moldings – carried out on pieces that included a weld line – we found that nanoclay induces changes in the morphology developed upon processing . It enhances molecular orientation induced by flow increasing the level of crystalline phase orientation in the flow direction.…”
Section: Introductionmentioning
confidence: 95%
“…[12] In our previous investigations conducted on PP/organoclay nanocomposite moldingscarried out on pieces that included a weld linewe found that nanoclay induces changes in the morphology developed upon processing. [13][14][15] It enhances molecular orientation induced by flow increasing the level of crystalline phase orientation in the flow direction. To find out the influences of the weld lines and of the complex flow upon final properties, fracture toughness was evaluated at different locations of the parts and a spatial distribution of toughness was found.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reproduce in-service conditions, the impact performance was assessed by means of uniaxial tensile (in-plane) and biaxial flexural (out-of-plane) tests [69] (Figure 6.6). In order to reproduce in-service conditions, the impact performance was assessed by means of uniaxial tensile (in-plane) and biaxial flexural (out-of-plane) tests [69] (Figure 6.6).…”
Section: Uniaxial Tensile and Biaxial Flexural Impact Testsmentioning
confidence: 99%
“…Visual inspection of biaxially impacted samples showed that the orientation of polymer molecules and clay platelets induced by melt flow prevailed, and the weldline was not the determinant of the toughness of the moldings (Figure 6.8). Cracking along the weldline results from less macromolecular interpenetration and chain entanglement, and unfavorable nanoparticle orientation [69]. The same moldings were fractured using mode-I double-edge-notched tensile specimens.…”
Section: The Effect Of Injection-molding Processing Conditions On Thementioning
confidence: 99%
“…Manufacturing of PP/ nanoclay composites using conventional injection moulding (CIM) is not an easy task. Mouldings usually displayed poor nanoclay dispersion since the imposed thermomechanical conditions do not generate large enough stress fields to deagglomerate/ exfoliate the clay agglomerates completely [7] and [8]. Besides poor dispersion, the presence of voids and defects in thick specimens is a common feature in many industrial mouldings.…”
Section: Introductionmentioning
confidence: 99%